2019
DOI: 10.1002/jpen.1536
|View full text |Cite
|
Sign up to set email alerts
|

RW‐2018—Research Workshop: The Effect of Nutrition on Epigenetic Status, Growth, and Health

Abstract: The goal of the 2018 American Society for Parenteral and Enteral Nutrition (ASPEN) Research Workshop was to explore the influence of nutrition and dietary exposure to xenobiotics on the epigenome during critical periods in development and how these exposures influence both disease incidence and severity transgenerationally. A growing compendium of research indicates that the incidence and severity of common and costly human diseases may be influenced by dietary exposures and deficiencies that modify the epigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Although several diseases are caused by genetic factors, i.e., by alterations in the DNA sequence, a large number of diseases are now influenced by environmental factors that cause chemical modifications of the DNA by epigenetic mechanisms without altering its sequence [ 82 ]. The effects of environmental factors on the epigenome are more prominent and could shape adult phenotypes when the exposure to these factors happens early in life during critical periods of development, such as prenatal, postnatal, childhood and early adulthood [ 83 ].…”
Section: Early-life Nutrition and Mental Healthmentioning
confidence: 99%
“…Although several diseases are caused by genetic factors, i.e., by alterations in the DNA sequence, a large number of diseases are now influenced by environmental factors that cause chemical modifications of the DNA by epigenetic mechanisms without altering its sequence [ 82 ]. The effects of environmental factors on the epigenome are more prominent and could shape adult phenotypes when the exposure to these factors happens early in life during critical periods of development, such as prenatal, postnatal, childhood and early adulthood [ 83 ].…”
Section: Early-life Nutrition and Mental Healthmentioning
confidence: 99%
“…Verlinden I et al reported that PN induced DNA methylation disruption in the 2- to 4-year-old pediatric population, independent of gestational age at birth [ 16 ]. A recent workshop (2018) by the American Society for Parenteral and Enteral Nutrition (ASPEN) reported that the quality of nutrition in early childhood and exposure to xenobiotics could increase the risk of developing metabolic diseases such as diabetes, obesity, hypertension, cardiovascular diseases, and even mental illness [ 37 ]. PN is a source of xenobiotics, such as H 2 O 2 , lipid aldehydes and organic peroxides [ 8 , 9 , 38 , 39 ], all of which interfere with glutathione, thus weakening the child’s antioxidant defense.…”
Section: Discussionmentioning
confidence: 99%
“…The epigenome can be shaped by nutritional states [93,94]. Susceptibility occurs particularly at the time when critical developmental processes are taking place, but also in adulthood diet can affect epigenetic marks.…”
Section: The Epigenetic Legacy Of Icu Feedingmentioning
confidence: 99%